2001
DOI: 10.1136/ip.7.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Dog bite and injury prevention—analysis, critical review, and research agenda

Abstract: Objectives-To analyze Australian dog bite injury data and make international comparisons; to review risk and protective factors relating to the dog, injured person, and environment; and to recommend action for prevention and research. Methods-Australian dog bite injury data, complemented by detailed Victorian and regional data from routine health records and vital statistics, were analyzed to determine incidence, severity, nature, circumstances, and trends. International comparison data were extracted from pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
2
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 19 publications
12
98
2
11
Order By: Relevance
“…1,2 In the United States, 4.7 million people were estimated to have been bitten by dogs in 1994 (an incidence rate of 16.1/1000 in adults and 24.5/1000 in children), of whom 800,000 required medical treatment. 3 The annual estimated number of dog bites in India is 17.4 million, leading to estimated 18,000-20,000 cases of human rabies per year.…”
mentioning
confidence: 99%
“…1,2 In the United States, 4.7 million people were estimated to have been bitten by dogs in 1994 (an incidence rate of 16.1/1000 in adults and 24.5/1000 in children), of whom 800,000 required medical treatment. 3 The annual estimated number of dog bites in India is 17.4 million, leading to estimated 18,000-20,000 cases of human rabies per year.…”
mentioning
confidence: 99%
“…Increased dog bite incidents in children is considered a behavioral risk because of their extreme curiosity, lack of inhibition, limited knowledge and experience about dog behavior, and inability to protect themselves from an attack. 4 It has also been suggested that bitesin children are more likely to be reported than in adults because of more parental concern towards children or the severity of theirinjuries. However, it is also believed that children in developing countries do not report minor bites or scratches to their parents, which increases the risk of rabies infection.…”
Section: Resultsmentioning
confidence: 99%
“…washing with soap and water) and rabies can also be integrated into the elementary school curriculum to educate children on the public health hazard of dog bites. 4 Australia, Chapman et al demonstrated that children who had been educated and provided information on ways to approach dogs displayed appreciably greater precautionary behaviors than children that did not receive any awareness education on dog behaviors and intervention. 5 Therefore, dog bite preventive education is important in children.…”
Section: Resultsmentioning
confidence: 99%
“…A associação de indivíduos desta faixa etária ao sexo masculino pode ser explicada pela maior atividade, maior oportunidade de encontro com os animais no espaço social que ocupam, e ainda brincadeiras e atitudes bruscas que possam despertar a reação agressiva do animal (GARCIA et al, 1999). Nossos resultados condizem com outros estudos, onde as crianças, juntamente com sexo masculino e local da residência das vítimas, são considerados fatores de risco para acidentes por mordedura de cães (OZANNE-SMITH et al, 2001, LIPPOLIS et al, 2004.…”
Section: Acidentes Por Mordeduras De Cães E Gatos No Município De Pinunclassified